Ready for School? Effects on School Starters of Establishing School Psychology Offices in Norway - Martin Flatø; Bernt Bratsberg; Andreas Kotsadam; Fartein Ask Torvik; Ole Røgeberg; Camilla Stoltenberg (Center for Economic Studies and ifo Institute (CESifo), 2023)
We consider long-term impacts of establishing school psychology offices in Norway, which introduced 'maturity testing' to advice parents and school boards on school starting age. In the early reform period, children born close to the normative age cut-off who reached school-starting age after the establishment were more likely to finish compulsory schooling late, and experienced higher earnings as adults. When offices were instead able to block delayed school entry after a legislative change, having an office in operation led to a reduction in the likelihood of late graduation for the youngest children in each cohort, and no long-term benefits.
Keywords: I21; I24; I26; I28; J24; N34; 330; school psychology; maturity; school readiness; redshirting; school starting age; Norway